Komunikasi Interpersonal Antar Orang Tua Dan Anak Terhadap Karakter Anak - Haliza Lufipah; Bayu Pamungkas; Mulki Pasha Haikal (Kampret Journal, 2022)
Research on this problem aims to understand the interpersonal communication of parents on the character of their children to build an effective communicative attitude, and to develop children's communication skills in the family environment and in the community, so that parental communication can be open and easy to understand. The research method used is a qualitative approach with descriptive analysis of qualitative data. The data used is through in-depth interviews with two informants, namely the father and mother. The results of research conducted from the results of theories associated with the results of interviews that obtain and explain that some parents want their children to be more open and consider their children as friends to improve the quality of two-way interpersonal communication in children towards the character of the child so that interpersonal communication is always always done by parents, the child's character becomes more confident and always open.